Polymer Processing under Microwaves - Kedafi Belkhir; Guillaume Riquet; Frédéric Becquart (Advances in Polymer Technology)
Over the last decades, microwave heating has experienced a great development and reached various domains of application, especially in material processing. In the field of polymers, this unusual source of energy showed important advantages arising from the direct microwave/matter interaction. Indeed, microwave heating allows regio-, chemio-, and stereo-selectivity, faster chemical reactions, and higher yields even in solvent-free processes. Thus, this heating mode provides a good alternative to the conventional heating by reducing time and energy consumption, hence reducing the costs and ecological impact of polymer chemistry and processing. This review states some achievements in the use of microwaves as energy source during the synthesis and transformation of polymers. Both in-solution and free-solvent processes are described at different scales, with comparison between microwave and conventional heating.